2015
DOI: 10.1016/j.physio.2015.03.3516
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital-based and community based models of cerebral palsy rehabilitation: a quasi-experimental study

Abstract: Background: Cerebral palsy requires appropriate on-going rehabilitation intervention which should effectively meet the needs of both children and parents/care-givers. The provision of effective support is a challenge, particularly in resource constrained settings. A quasi-experimental pragmatic research design was used to compare the impact of two models of rehabilitation service delivery currently offered in Harare, Zimbabwe, an outreach-based programme and the other institution-based. Method: Questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…15 This study used an adapted tool 13 and, although the output of the level of satisfaction questionnaire was overall positive and valuable as it directly impacts treatment outcomes, 3 the exploratory discussions highlighted significant areas for assisting the rehabilitation of children living with CP by advocating the view of the caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15 This study used an adapted tool 13 and, although the output of the level of satisfaction questionnaire was overall positive and valuable as it directly impacts treatment outcomes, 3 the exploratory discussions highlighted significant areas for assisting the rehabilitation of children living with CP by advocating the view of the caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In an analogous resourcelimited African setting a study revealed that caregivers of children with CP need added financial and emotional support. 3 Researchers in the study adopted a decentralised community approach by basing the study at the clinics; this negated the environmental limitations, improved social support and improved the outcomes of a rehabilitation intervention programme compared with an institutional based health setting making specific appointments for rehabilitation sessions. 3 This is supported by another South African study advocating that community-based interventions provide psychosocial support, support relationships and improve social functioning and selfesteem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations